2020
DOI: 10.3390/nu12092657
|View full text |Cite
|
Sign up to set email alerts
|

Association between Bone Turnover Markers, Leptin, and Nutritional Status in Girls with Adolescent Idiopathic Scoliosis (AIS)

Abstract: The link between scoliotic deformity and bone metabolism in adolescent idiopathic scoliosis (AIS) has not been well researched. Moreover, the data concerning the cross-talk between fat tissue content/hormonal activity and bone markers in this group of patients are lacking. The aim of the study was to assess whether there exists a significant relationship between the severity of AIS and bone turnover markers and leptin levels. The study group was consisted of 77 AIS girls, aged 14.7 ± 2.17 years. Scoliotic curv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 45 publications
(58 reference statements)
0
12
0
7
Order By: Relevance
“…A cross-sectional study [ 26 ] was conducted with the aim of correlating the extent of the severity of the scoliotic curve with markers of bone turnover (osteocalcin (OC) and amino terminal collagen (NTx) crosslinks with respect to leptin level and nutritional status in girls with AIS 77 girls were included in this study with newly diagnosed scoliosis, aged 14.7 ± 2.17 years, divided into three groups based on the Cobb angle detected on radiography (mild scoliosis 10–19°, moderate scoliosis 20–39°, severe scoliosis ≥ 40°). Corrected height, weight and circumferences of waist and hip were measured and BMI, corrected height Z-score, BMI Z-score were calculated (standard deviation number from the 50th percentile) and the waist-to-height ratio (WHtR) for the whole group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A cross-sectional study [ 26 ] was conducted with the aim of correlating the extent of the severity of the scoliotic curve with markers of bone turnover (osteocalcin (OC) and amino terminal collagen (NTx) crosslinks with respect to leptin level and nutritional status in girls with AIS 77 girls were included in this study with newly diagnosed scoliosis, aged 14.7 ± 2.17 years, divided into three groups based on the Cobb angle detected on radiography (mild scoliosis 10–19°, moderate scoliosis 20–39°, severe scoliosis ≥ 40°). Corrected height, weight and circumferences of waist and hip were measured and BMI, corrected height Z-score, BMI Z-score were calculated (standard deviation number from the 50th percentile) and the waist-to-height ratio (WHtR) for the whole group.…”
Section: Resultsmentioning
confidence: 99%
“…Idiopathic scoliosis has a high incidence among children all over the world and its multifactorial etiology is now accepted, although to date it is not fully known [ 16 , 23 , 27 , 28 ]. This condition can lead to important changes in the child’s physical appearance with a negative psychological effect on it [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, scattered evidence has suggested that one’s metabolism and energy homeostasis is involved in AIS risk, severity, or progression [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Although interesting, this hypothesis has yet been poorly explored.…”
Section: Introductionmentioning
confidence: 99%